Evaluation of Antiradical and Antioxidant Activities of Lipopeptides Produced by Bacillus subtilis Strains - Dussert, Elodie; Tourret, Mélissa; Dupuis, Chloé; Noblecourt, Alexandre; Behra-Miellet, Josette; Flahaut, Christophe; Ravallec, Rozenn; Coutte, François (Frontiers in Microbiology, 2022)
This study investigated the antiradical and antioxidant potential of the three families of lipopeptides (i.e., surfactin, mycosubtilin, and plipastatin/fengycin) produced by Bacillus subtilis strains. The antiradical/antioxidant activities of highly purified lipopeptides were studied in acellular models using a 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, superoxide anion (O2.-), hydrogen peroxide, (H2O2) and hydroxyl radical (HO.). At a lipopeptide concentration of 500 mg.L−1, the maximum inhibition of DPPH reached 22.88% (obtained for plipastatin). Moreover, the scavenging effects of O2.-, H2O2, and HO. at the highest concentration tested (250 mg.L−1) were found to be 6, 21, and 3% for surfactin, 19, 9, and 15% for mycosubtilin, 21, 18, and 59% for plipastatin, 21, 31, and 61% for the mixture of surfactin/plipastatin, and 13, 16, and 15% for the mixture of surfactin/mycosubtilin, respectively. These results showed that plipastatin was the best candidate due to its antioxidant activities.